Signifikansi YouTube Sebagai Medium Pewartaan Injil bagi Generasi Milenial di Indonesia - David Eko Setiawan (Institut Agama Kristen Negeri Toraja, 2021)
The rapid development of information technology has given rise to a variety of social media platforms that can connect many people from all walks of life, and in all places quickly. In various studies show that most users of the platform have the millennial generation. Freedom and speed to access it is a consideration for the use of social media as a medium for proclaiming the gospel. YouTube as a social media platform, very popular with millennials, can help evangelists in communicating it attractively, creatively, interactively, and inspiratively. The problem with this research is how is the significance of YouTube as a medium for evangelism for the millennial generation in Indonesia? While the purpose of this study is to explain the significance of YouTube as a medium for proclaiming the gospel for the millennial generation in Indonesia. In this study, it was found that basically, YouTube is significant as a medium for proclaiming the gospel for the millennial generation in Indonesia because it is in accordance with the context of those who like social media platforms that are attractive, creative, interactive, and inspiring.Perkembangan teknologi informatika yang begitu cepat memunculkan berbagai platform media sosial yang dapat menghubungkan banyak orang dari segala lapisan, dan di segala tempat secara cepat. Dalam berbagai penelitian menunjukkan bahwa pengguna terbanyak dari platform tersebut ada generasi milenial. Kebebasan dan kecepatan untu mengaksesnya, menjadi pertimbangan pemanfaatan media sosial sebagai medium pewartaan Injil. YouTube sebagai salah satu platform media sosial, sangat digemari oleh generasi milenial, dapat menolong pewarta injil dalam mengkomunikasikannya secara atraktif , kreatif, interatif dan inspiratif. Masalah penelitian ini adalah bagaimanakah signifikansi YouTube sebagai medium pewartaan Injil bagi generasi milenial di Indonesia? Sedangkan tujuan penelitian ini adalah untuk menjelaskan signifikansi YouTube sebagai medium pewartaan Injil bagi generasi milenial di Indonesia. Pada penelitian ini ditemukan bahwa pada dasarnya YouTube signifikan sebagai medium pewartaan Injil bagi generasi milenial di Indonesia karena sesuai dengan konteks mereka yang menggemari platform media sosial yang atraktif, kreatif, interatif dan inspiratif.